2015
DOI: 10.1037/tps0000046
|View full text |Cite
|
Sign up to set email alerts
|

To grab and to hold: Cultivating communal goals to overcome cultural and structural barriers in first-generation college students’ science interest.

Abstract: Homogeneity within science limits creativity and discovery, and can feed into a perpetuating cycle of underrepresentation. From enhancing social justice to alleviating health and economic disadvantages, broadening participation in science is imperative. We focus here on first-generation students (FGS) and identify factors which grab and hold science interest among this underrepresented group. Might the culture and norms within science unintentionally limit FGS' participation? We argue that two distinct aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 30 publications
(70 reference statements)
2
65
0
Order By: Relevance
“…Among self‐reporting surveys, one of the most commonly referenced and used/modified instruments is known as the Situational Interest Survey (Linnenbrink‐Garcia et al ., ). Multiple researchers have used this instrument in an effort to investigate SI in a variety of contexts (see Allen, Muragishi, Smith, Thoman, & Brown, ; Corkin, Yu, Wolters, & Wiesner, ; Plass et al ., ; Stoel, van Drie, & van Boxtel, ), but self‐reporting methodologies invite criticism of reliability. In light of more advanced technologies developing in neuroscience, Hidi () called for integrating research across fields to better understand macro‐level questions of motivation, like SI.…”
Section: Situational Interestmentioning
confidence: 99%
“…Among self‐reporting surveys, one of the most commonly referenced and used/modified instruments is known as the Situational Interest Survey (Linnenbrink‐Garcia et al ., ). Multiple researchers have used this instrument in an effort to investigate SI in a variety of contexts (see Allen, Muragishi, Smith, Thoman, & Brown, ; Corkin, Yu, Wolters, & Wiesner, ; Plass et al ., ; Stoel, van Drie, & van Boxtel, ), but self‐reporting methodologies invite criticism of reliability. In light of more advanced technologies developing in neuroscience, Hidi () called for integrating research across fields to better understand macro‐level questions of motivation, like SI.…”
Section: Situational Interestmentioning
confidence: 99%
“…We also recommend that faculty emphasize the altruistic goals inherent in STEM in order to change students' often-stereotypical perceptions about STEM careers--stereotypes which often preclude interest in STEM careers (Finson, 2010;Losh 2009). Since some cultural minority groups (e.g., Latino, Native American, and the Deaf community) value careers that afford opportunities to give back to their communities, elaborating on explicit connections between science and these communities may increase interest in STEM careers Allen et al, 2015;Brown et al, 2015;Diekman et al, 2010;Thoman, et al, 2015). More work is needed to challenge students' science identities and improve interest in STEM careers if these types of courses are to increase recruitment into STEM majors.…”
Section: Discussionmentioning
confidence: 99%
“…When a student accepts this stereotype, she effectively precludes her potential interest in a STEM career as her self-perception does not align with her perceptions of who scientists are; thus, for her, a STEM career is unimaginable (Losh, 2009). These stereotypes disproportionately affect women, people of color, first-generation students, and students of low socio-economic status, all of whom tend to highly value altruistic career goals, but who do not perceive STEM as affording opportunities to satisfy altruistic goals (Allen et al, 2015;Brown, Thoman, Smith, & Diekman, 2015;Diekman et al, 2010;Thoman, Brown, Mason, Harmsen, & Smith;. Moreover, cultural communities (e.g., Latino and Native Marchut American communities ) often encourage the pursuit of altruistic goals that benefit one's community.…”
mentioning
confidence: 99%
“…Although there was no explicit gender language used in these syllabi, Parson demonstrated that the syllabi created a potentially hostile climate for women by promoting individualistic, masculine values. It could easily be argued that the same White male-centric language that Parson identified could be off-putting to students who are from more communal backgrounds, as are many SOC (Allen, Muragishi, Smith, Thoman, & Brown, 2015). A more communal language that emphasizes relationship and connection in contrast to male-centric language that emphasizes individualism and hierarchy supports the creation of a collaborative and inclusive environment.…”
Section: Syllabus Best Practicesmentioning
confidence: 99%